Imaging tropical peatlands in Indonesia using ground penetrating radar (GPR) and electrical resistivity imaging (ERI): implications for carbon stock estimates and peat soil characterization - Comas, X.; Terry, N.; Slater, L.; Warren, M.; Kolka, R.; Kristijono, A.; Sudiana, N.; Nurjaman, D.; Darusman, T. (Copernicus GmbH, 2015)
Abstract. Current estimates of carbon (C) storage in peatland systems worldwide indicate that tropical peatlands comprise about 15% of the global peat carbon pool. Such estimates are uncertain due to data gaps regarding organic peat soil thickness, volume and C content. We combined a set of indirect geophysical methods (ground-penetrating radar, GPR, and electrical resistivity imaging, ERI) with direct observations using core sampling and C analysis to determine how geophysical imaging may enhance traditional coring methods for estimating peat thickness and C storage in a tropical peatland system in West Kalimantan, Indonesia. Both GPR and ERI methods demonstrated their capability to estimate peat thickness in tropical peat soils at a spatial resolution not feasible with traditional coring methods. GPR is able to capture peat thickness variability at centimeter-scale vertical resolution, although peat thickness determination was difficult for peat columns exceeding 5 m in the areas studied, due to signal attenuation associated with thick clay-rich transitional horizons at the peat–mineral soil interface. ERI methods were more successful for imaging deeper peatlands with thick organomineral layers between peat and underlying mineral soil. Results obtained using GPR methods indicate less than 3% variation in peat thickness (when compared to coring methods) over low peat–mineral soil interface gradients (i.e., below 0.02°) and show substantial impacts in C storage estimates (i.e., up to 37 MgC ha−1 even for transects showing a difference between GPR and coring estimates of 0.07 m in average peat thickness). The geophysical data also provide information on peat matrix attributes such as thickness of organomineral horizons between peat and underlying substrate, the presence of buried wood, buttressed trees or tip-up pools and soil type. The use of GPR and ERI methods to image peat profiles at high resolution can be used to further constrain quantification of peat C pools and inform responsible peatland management in Indonesia and elsewhere in the tropics.